General Formation of M–MoS3 (M = Co, Ni) Hollow Structures with Enhanced Electrocatalytic Activity for Hydrogen Evolution. Issue 1 (5th November 2015) - Yu, Le; Xia, Bao Yu; Wang, Xin; Lou, Xiong Wen
Abstract : Complex molybdenum‐based ternary or multinary sulfides hollow structures are developed via a fast precipitation process, together with a subsequent annealing treatment. Benefiting from the merits of high‐curvature surfaces with excellent intrinsic catalytic activity, the obtained unique hollow structures exhibit enhanced performance as electrocatalysts for hydrogen production in acidic media.